Demystifying Pedagogic Discourse of Indonesian Language In-Service Teachers in the Pre-Teaching Phase of Communication - Sastromiharjo, Andoyo; Ansas, Velayeti Nurfitriana; Mulyati, Yeti; Damaianti, Vismaia S. (Universitas Negeri Makassar, 2025)
This study explored the pedagogical discourse of experienced Indonesian language teachers (in-service teachers) during the pre-teaching phase, focusing on the communication strategies used when initiating classroom learning activities because initial teacher-student interactions are crucial for shaping engagement and motivation. The qualitative research investigated how teachers designed their communication to create an effective learning environment based on the Learning Activity Framework. The study involved 20 in-service Indonesian language teachers, with data collected through classroom observations. The results revealed that teachers' communication patterns included engaging, focusing, contextualising, modeling, establishing expectations, and goal orientation cycles. Teachers applied two pedagogical communication strategies in each cycle to set learning goals, build interpersonal relationships, and activate students' prior knowledge. These strategies were also used to set expectations, manage classroom rules, and apply interactive questioning to encourage participation. Because teachers play cognitive and emotional roles, their initial communication significantly influences students' readiness and motivation. This study contributes to understanding pedagogical discourse in Indonesian classrooms and emphasises the importance of the pre-teaching phase as a foundation for effective teaching. The findings suggest the need for teacher professional development that emphasises reflective communication to support meaningful student engagement